Sperm bundles in the seminal vesicles of sexually mature Lasius ant males. - William E Burnett; Jürgen Heinze (PLoS ONE, 2014)
In many insects, sperm cells are produced in bundles with their heads being held together by a glycoprotein matrix secreted by a cyst cell. Mature sperm cells in the seminal vesicles are usually free, but in sawflies and several other insects, such structures (spermatodesmata) remain intact and sperm cells may be ejaculated as bundles. Here we report the occurrence of spermatodesmata in mature males of the ant Lasius pallitarsis. Microscopic investigations of the abdominal contents of males immediately prior to their nuptial flights showed that the anterior ends of numerous sperm cells were embedded in an oval-shaped 20 by 30 micrometer extracellular fibrous cap. Individual sperm ranged in length from 55 to 75 micrometers with an average overall length of 65 micrometers. The bulb-shaped heads of the sperm were relatively small, only about 1.5 micrometers in length and about 1.1 micrometers in diameter. The diameter of the sperm tails was approximately 1 micrometer. Observations of live preparations of the spermatodesmata showed increasingly active undulating wave-like movement of the sperm tails as the slide preparations aged. This appears to be the first case of sperm bundles being present in the seminal vesicles of mature ant males--males that are immediately poised to complete their nuptial mating flight.